ANALISIS MANAJEMEN PERSEDIAAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY DAN REORDER POINT DALAM PENGENDALIAN PERSEDIAAN GAS LPG 3 KG PADA SPBE PT.BCP CIREBON - Sanni El Randi, Tuti Ratnawati; Meirini, Dianita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Management accounting in inventory management is critical in determining theamount of inventory by company management. Demand rises and falls as a resultof public demand. When the price of 3 kg LPG gas rises due to increased publicdemand, it can cause a shortage of goods, resulting in price instability in themarket. The aim of this study was to determine the analysis of 3 kg LPG gasinventory management in determining the optimal quantity using the EconomicOrder Quantity (EOQ) method, determining the right Reorder Point (ROP),efficient total inventory-costs, and safety stock inventories in controlling thesupply of LPG gas at SPBE PT BCP Cirebon. This study utilized the descriptive qualitative research method with primary and secondary data sources. Theconclusion shows that (EOQ) and (ROP) methods are more effective and efficientif they can be applied to SPBE PT BCP. The average purchase quantity of themost optimal inventory EOQ method is 58,092 kg with a frequency of 184 timesper year, safety stock quantity is 102,900 kg, ROP will be conducting if theremaining inventory is 138,214 kg, and the total cost of inventory is more efficientat Rp. 61,037,316.6